A study on the discomfort of virtual reality glasses: A systematic review - Antônio Althoff Bolan, Giácomo; Pozzebon, Eliane; Reis de Sá Júnior, Antônio (International Seven Journal of Health Research, 2024)
The aim of this article is to present a systematic review of the literature on technological innovations in the use of Virtual Reality glasses and possible discomfort. Based on concepts such as “cybersickness” and “motion sickness”, we will have a starting point for deepening our knowledge of the effects of using virtual reality glasses, such as nausea, headaches and others. The methodology used in this systematic review and bibliometric analysis focused on the discomfort associated with wearing virtual reality (VR) glasses. The research adopted a quantitative analysis of the data and information available on the subject, with the aim of understanding the effects such as nausea, headaches, among others, when using VR glasses. The results obtained in the review addressed various aspects of VR use, including the promise of immersive VR being safe and effective for application in the elderly, with no significant records of symptoms of simulation sickness. The research highlighted the importance of understanding user needs and satisfaction in the process of designing and implementing VR solutions, highlighting how VR can play a significant role in a variety of contexts, from pre-occupancy assessment in the elderly to training and reducing symptoms of kinetosis using VR technologies. In addition, it was investigated whether individual characteristics of balance and tendency to kinetosis are related to vulnerability to cyber sickness, a side effect caused by the use of virtual reality with head-mounted displays. In summary, this systematic review has contributed to the understanding of the discomfort associated with the use of VR glasses, exploring strategies to minimize adverse effects and improve the user experience, with the aim of increasing the adoption of this technology in various areas. O objetivo deste artigo é apresentar uma revisão sistemática da literatura sobre inovações tecnológicas quanto a utilização dos óculos de Realidade Virtual e o possível desconforto. A partir dos conceitos como “cybersickness” e “motion sickness”, teremos um ponto inicial para aprofundarmos o conhecimento sobre os efeitos, como de enjoos, dores de cabeças dentre outros quando da utilização dos óculos de realidade virtual. A metodologia empregada nesta revisão sistemática e análise bibliométrica focou no desconforto associado ao uso de óculos de realidade virtual (RV). A pesquisa adotou uma análise quantitativa dos dados e informações disponíveis sobre o tema, visando compreender os efeitos como náuseas, dores de cabeça, entre outros, quando da utilização dos óculos de RV. Os resultados obtidos na revisão abordaram diversos aspectos do uso da RV, incluindo a promessa da RV imersiva ser segura e eficaz para aplicação em idosos, sem registros significativos de sintomas de doença de simulação. A pesquisa destacou a importância de compreender as necessidades e satisfação dos usuários no processo de design e implementação de soluções em RV, evidenciando como a RV pode desempenhar um papel significativo em contextos variados, desde a avaliação de pré-ocupação em idosos até o treinamento e redução dos sintomas da cinetose usando tecnologias de RV. Além disso, foi investigado se características individuais do equilíbrio e tendência à cinetose estão relacionadas à vulnerabilidade à doença cibernética, um efeito colateral causado pelo uso de realidade virtual com displays montados na cabeça. Em suma, esta revisão sistemática contribuiu para a compreensão do desconforto associado ao uso de óculos de RV, explorando estratégias para minimizar os efeitos adversos e melhorar a experiência do usuário, com o objetivo de aumentar a adoção dessa tecnologia em diversas áreas.